Engineering harmony under multi-constraint objectives: the perspective of meta-analysis - Wang, Qiankun; Zuo, Weiwei; Li, Qianyao (Journal of Civil Engineering and Management, 2020)
Harmony is the process of coordinated development between the elements, subsystems and the environment in each Engineering stage of the engineering implementation. Quality, duration, cost and risk are the key factors to achieve engineering harmony. Clarifying the influencing factors of engineering harmony and its mechanism can improve the possibility of success. The meta-analysis method is used to carry out a restudy of existing researches of engineering harmony. First, quality, duration, cost and risk are selected as the variables of achieving engineering harmony. Second, the paper collects 29 existing researches including many countries and regions around the world on the relationship between the variables and engineering harmony. Third, each value is calculated and corrected according to literature coding. Forth, publication deviation and total effect test are checked. Finally, the research conclusions and engineering management implications are given based on the results of meta-analysis. The results show that quality objective, duration objective, cost objective and risk management objective all have positive impact on achieving engineering harmony. The engineering type has no regulatory effect on positive impact of the duration objective and cost objective, but has regulatory effect on positive impact of the quality objective and risk management objective on the engineering harmony.First published online 23 January 2020